Multiphysics in Nanostructures - Umeno, Yoshitaka; Shimada, Takahiro; Kinoshita, Yusuke; Kitamura, Takayuki (Springer Japan : Imprint: Springer, 2017)
This is the first book to systematically review and summarize the recent rapid advances and varied results of multiphysics in nanoscale materials including elastic strain engineering. This book comprises topics on remarkable properties of multiphysics in low-dimensional nanoscale components from first-principles density-functional theory (or tight binding) calculations, which are essential for the nonlinear multiphysics couplings due to quantum mechanical effects. This volume provides a clear point of view and insight into the varied work done in diverse fields and disciplines and promotes a fundamental to state-of-the-art understanding of properties of multiphysics. Because the novelty and complexity of mechanical and multiphysical properties of low-dimensional nanostructures originate from combinations of outer shapes (e.g., films, wires, tubes, and dots) and inner understructures (e.g., grain boundaries, domain walls, vacancies, and impurities), the nanostructures are classified into fundamental elements, and the properties of each element and their interplay are reviewed for systematic, in-depth understanding. This book points out a new direction for multiphysics in nanostructures, which opens the door both to exploiting and to designing novel functionalities at the nanoscale. Readers will be interested in this rapidly expanding multidisciplinary work and will be motivated to enter this promising research area.
Keywords: Materials science.; Physics.; Nanoscale science.; Nanoscience.; Nanostructures.; Nanotechnology.; elektronické knihy; electronic books